Diagnostic Yield of Fiber Optic Bronchoscopy and CECT Thorax in Patients of Haemoptysis with Normal Chest X-Ray - Agarwala, Abinash; Basuthakur, Sumitra; Shamim, Shelley; Saha, Kaushik; Bhattacharya, Sujit; Sengupta, Amitabha (International Journal of Medical Research and Review, 2015)
Introduction: Contrast enhanced computed tomography (CECT) thorax & Fibre Optic Bronchoscopy (FOB) are main investigations in patients of hemoptysis with normal chest X-ray. But there are limited data on their diagnostic yield especially from South East Asia. Methods: An observational study on 60 patients with hemoptysis with normal chest X -ray was conducted from April 2012 to April 2014. CECT thorax and FOB were done in all of them. Results: Out of 60 patients 38 (63.3%) were male with even age distribution. Yield of CECT was 40% (24 patients) and main diagnosis were bronchiectesis (25%) and tuberculosis (11.6%). Diagnostic yield of FOB was 47% (28 patients) with predominant diagnosis of tuberculosis (18.33%), bronchitis (18.33%) and bronchogenic carcinoma (6.66%). Overall diagnostic yield was 76.6% (46 cases). Bronchogenic carcinoma cases were all male smokers and 3 of them were more than 40 years old. Conclusion: CECT thorax and FOB are complimentary to each other in evaluation of hemoptysis with normal chest x-ray. Bronchogenic carcinoma and tuberculosis cases require specific treatment and they were diagnosed in confirm way only by FOB. So, FOB have advantage over CT scan, especially among patients with increased risk of bronchogenic carcinoma (male-smokers with age > 40 years).